2015
DOI: 10.1137/140998676
|View full text |Cite
|
Sign up to set email alerts
|

Delayed Feedback Versus Seasonal Forcing: Resonance Phenomena in an El Nin͂o Southern Oscillation Model

Abstract: Climate models can take many different forms, from very detailed highly computational models with hundreds of thousands of variables, to more phenomenological models of only a few variables that are designed to investigate fundamental relationships in the climate system. Important ingredients in these models are the periodic forcing by the seasons, as well as global transport phenomena of quantities such as air or ocean temperature and salinity. We consider a phenomenological model for the El Niño Southern Osc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(43 citation statements)
references
References 59 publications
1
40
0
Order By: Relevance
“…Additionally, the smooth system contains period doubling bifurcations, which we do not observe in our system, likely due to the loss of nonlinearity in the limit of κ → ∞. However, the analysis presented here does provide new insights into dynamics previously observed numerically 16,17 .…”
Section: Discussionsupporting
confidence: 50%
See 2 more Smart Citations
“…Additionally, the smooth system contains period doubling bifurcations, which we do not observe in our system, likely due to the loss of nonlinearity in the limit of κ → ∞. However, the analysis presented here does provide new insights into dynamics previously observed numerically 16,17 .…”
Section: Discussionsupporting
confidence: 50%
“…We label solutions by the characteristic ratio P :R, where R is the number of times the trajectory crosses from x < 0 to x > 0 in one cycle. Note that the P : R notation differs from the p : q notation used in some previous literature 17,18 , where p q is the rotation number. We find that P : R is a useful measure of a solution, for reasons that will be made clear later.…”
Section: B Sample Solutionsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this section we perform numerical simulations of the system (1) with uniform and two-peak distribution kernels, given by (19) in order to compare theoretical predictions for switching times. Following the same methodology as in [41], we calculate the mean switching times T st as the noise η(t) takes the system out of the basin of attraction of the steady state x A to x < x S .…”
Section: Numerical Simulationsmentioning
confidence: 99%
“…In addition to intrinsic time delays, majority of real systems are also affected by both external and internal random perturbations, which necessitate the inclusion of noise into the dynamical models, and hence, stochastic differential delay equations (DDEs) are used to analyze a wide range of systems. For instance, gene regulatory networks are often modeled as stochastic birth-death processes with time delays [12], and anomalies during El Niño have been analyzed using delayed-oscillator models, excited by external weather noise [17][18][19]. Recently, time-delayed feedback control has been applied to noise-induced chimera states in FitzHugh-Nagumo networks with non-local coupling, and it has been shown that for some values of time delays, it can lead to the so-called period-two coherence resonance chimera [20].…”
Section: Introductionmentioning
confidence: 99%